Photoluminescence and Electron Paramagnetic Resonance Spectroscopy for Revealing Visible Emission of ZnO Quantum Dots - KIM HONG HEE; Lee, Heebin; Jeung Ku Kang; CHOI, WON KOOK (A H？thig, 2022)
Both PL and EPR are simultaneously adopted to systematically elucidate the defect centers of green luminescence (GL) as well as the EPR peak g = 1.96 of ZnO and the relationship between them. The PL of ZnO QDs reveals that GL of 2.21-2.31 eV disappears at excitation wavelengths > 400 nm. This is related to the electronic transition from conduction band (CB), or shallow donor defect centers, to deep defects of V-Zn-H complexes at approximate to 0.9 eV above the valence band (VB). The EPR peak g = 1.96 emerged only when irradiated with light shorter than 400 nm, which is explicitly correlated with the electrons trapped in the CB or the shallow donors participating in the GL. A spin-spin relaxation time (T-2) estimated from the peak-to-peak line width Delta H-pp in the EPR signal is approximate to 17.5-52.5 ns, which is two orders of magnitude longer than known values for bulk or thin-film ZnO.